THE URGENCY OF ADAPTING THE E-TAX SYSTEM TO TAX COMPLIANCE: INTEGRATION OF SATISFACTION LEVELS - Grace, Kezia; Olivia, Karyn; Mangoting, Yenni (Graduate Program of Universitas Tarumanagara, 2023)
The study investigated whether satisfaction levels play a role as a moderator in the correlation of adapting the e-tax system and tax compliance. The study used a quantitative method that tested e-tax system interactions and satisfaction with tax compliance. The study used survey method by distributing questionnaires through google form to personal taxpayers. The answers of 117 respondents were analyzed using Partial Least Square (PLS). The analytical tool used in research is WarpPls. The results showed that the e-tax system improves tax compliance. Moderation test results show that the interaction between satisfaction level and the e-tax system does not significantly influence the behavior of taxpayers using technology. In addition, taxpayers no longer only look at the usability and convenience offered by the digital administration system but consider other factors contained in the use of the system.